Rancang Bangun Buck Converter Efisiensi Tinggi Dengan Pengendali Arduino Nano Berbasis Simulasi Multisim 14.2 - Alfikri, Ahmad Mushawwir; Rahayu, Sofitri (KILAT, 2024)
A DC converter is needed to adjust the voltage generated by the PV cell so that it can be connected to the battery. DC converter devices have various efficiencies depending on the type of topology, as well as the selection of electronic components that make up the DC converter which has an impact on a lot of wasted energy in the electrical conversion process. According to Chapman (2005:105), the Buck Converter topology has an efficiency of up to 85%. A common challenge found in all types of DC converters is how to design a DC converter with high work efficiency. The author designed a Buck Converter with an efficiency of up to 90%, which can be integrated with a 20Wp PV Cell as input and a 12V50Ah VRLA Battery as output. The design begins by making a circuit simulation on the NI Multisim 14.2 software. Based on the simulation, a Buck Converter prototype was made with an Arduino Nano controller. Input Voltage Variation Test resulted that the maximum efficiency of the Buck Converter Simulation is 98% and the maximum efficiency of the Buck Converter Prototype is 92%. Duty Cycle Variation Test resulted that the maximum efficiency of Buck Converter Simulation is 99.3% and the maximum efficiency of Buck Converter Prototype is 96.4%. Load Variation Test resulted that the maximum efficiency of Buck Converter Simulation is 97.3% and the maximum efficiency of Buck Converter Prototype is 91.8%.